Axonal dysfunction in internal capsule is closely associated with early motor deficits after intracerebral hemorrhage in mice. (May 2016) - Hijioka, Masanori; Anan, Junpei; Matsushita, Hideaki; Ishibashi, Hayato; Kurauchi, Yuki; Hisatsune, Akinori; Seki, Takahiro; Katsuki, Hiroshi
Highlights: Hemorrhage in the internal capsule accompanies rapid appearance of motor deficits. Suppression of axonal transport may account for early motor deficits. Thrombin may mediate suppression of axonal transport after intracerebral hemorrhage. Abstract: Previously we showed that expansion of intracerebral hemorrhage (ICH) into the internal capsule greatly aggravated neurological symptoms in mice. Here we examined ICH-associated events in the internal capsule with relation to neurological dysfunction. Corticospinal axons labeled by biotinylated dextran amine exhibited fragmented appearance after ICH induced by local injection of collagenase into the internal capsule. Fragmentation of axonal structures was confirmed by neurofilament-H immunostaining, which was evident from 6 h after induction of ICH. We also observed accumulation of amyloid precursor protein, which indicated compromised axonal transport, from 3 h after induction of ICH. The early defect in axonal transport was accompanied by a robust decline in motor performance. Local application of an axonal transport inhibitor colchicine to the internal capsule induced a prompt decline in motor performance, suggesting that compromised axonal transport is closely associated with early neurological dysfunction in ICH. Arrest of axonal transport and fragmentation of axonal structures were also induced by local injection of thrombin, but not by thrombin receptor activator peptide-6, a protease-activated receptor-1 agonist. These results suggest that receptor-independent actions of thrombin mediate disruption of structure and function of axons by hemorrhage expansion into the internal capsule, which leads to severe neurological dysfunction.